BAZNAS’ ZAKAT MANAGEMENT PRIORITIES IN TIME OF POST COVID-19 PANDEMIC - Hartono, Haryani Santo (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
BAZNAS (The National Board of Zakat) as the only Indonesian government zakat institution is expected to become a trend setter for the development of zakat in the world's most popular Muslim country. The pandemic conditions that occurred all over the world have become a momentum for the rise of philanthropy including zakat as the heart of Islamic philanthropy. Generosity as a fundamental trait in humans has its own potential in the decisions many people share with others in the time of the crisis. This good habit becomes a very good opportunity even when entering the post-pandemic period. The reformulation of zakat management priorities in the post Covid-19 pandemic era is an important matter for discussion. BAZNAS together with the international world forum formulated zakat management priorities consisting of distribution, collection, and management improvement. BAZNAS adopts the zakat management priorities and adapts them to its main pillars.